Neuroimaging Insight Into Fragile X-Associated Neuropsychiatric Disorders: Literature Review - Elias-Mas, Andrea; Alvarez-Mora, Maria Isabel; Caro-Benito, Conxita; Rodriguez-Revenga, Laia (Frontiers in Psychiatry, 2021)
FMR1 premutation is defined by 55 to 200 CGG repeats in the Fragile X Mental Retardation 1 (FMR1) gene. FMR1 premutation carriers are at risk of developing a neurodegenerative disease called fragile X-associated tremor/ataxia syndrome (FXTAS). Nevertheless, neuropsychiatric disorders are the most common condition amongst FMR1 premutation carriers throughout their lifespan, and the denominations Fragile X-associated Neuropsychiatric Disorders (FXAND) and Fragile X-associated Neuropsychiatric Conditions (FXANC) have been proposed to bring recognition to these conditions. Herein, we reviewed the neuroimaging findings reported in relation with psychiatric symptomatology in adult FMR1 premutation carriers. A structured electronic literature search was conducted on FMR1 premutation and neuroimaging yielding a total of 3,229 articles examined. Of these, 7 articles were analyzed and are included in this review. The results showed that the main radiological findings among adult FMR1 premutation carriers presenting neuropsychiatric disorders were found on the amygdala and hippocampus, being the functional abnormalities more consistent and the volumetric changes more inconsistent among studies. From a molecular perspective, CGG repeat size, FMR1 mRNA and FMRP levels have been investigated in relation with the neuroimaging findings. Based on the published results, FMRP might play a key role in the pathophysiology of the psychiatric symptoms described among FMR1 premutation carriers.